Counseling services for international students in Japanese universities - Onishi, Akiko (Journal of International Students, 2026)
This study aimed to examine the current conditions of counseling services for international students at Japanese universities and identify challenges in improving these services. A survey was conducted among counseling centers at universities with at least 250 international students, with 63 institutions participating. Of those, approximately 30% reported changes to their support framework for international students in the past decade, and approximately half indicated that multilingual counseling services were available. In addition, the study examined the perceived challenges and measures taken in providing culturally competent services for international students. Based on these findings, this study has implications for practitioners and university leaders regarding the internationalization of student support services.